2018
DOI: 10.1155/2018/9274817
|View full text |Cite
|
Sign up to set email alerts
|

The Plant Proteinase InhibitorCrataBLPlays a Role in Controlling Asthma Response in Mice

Abstract: Background. CrataBL is a protein isolated from Crataeva tapia bark. It has been shown to exhibit several biological properties, including anti-inflammatory, analgesic, antitumor, and insecticidal activities. There are no studies evaluating the role of CrataBL in experimental asthma models. Aim. To evaluate the effects of CrataBL on lung mechanics, inflammation, remodeling, and oxidative stress activation of mice with allergic pulmonary inflammation. Materials and Methods. BALB/c mice (6-7 weeks old, 25-30g) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 54 publications
1
12
0
1
Order By: Relevance
“…These components are likely secreted due to the activation of fibroblasts and myofibroblasts, mainly because of the TGF-β signaling [57,58]. Collagen fibers are the most abundant elements of the ECM in the lung, constituting approximately 70% of the lung tissue, and changing the structure, quantity, or geometry of their distribution can trigger changes in lung functioning [58,59,60].…”
Section: Airway Remodeling In Asthmamentioning
confidence: 99%
See 1 more Smart Citation
“…These components are likely secreted due to the activation of fibroblasts and myofibroblasts, mainly because of the TGF-β signaling [57,58]. Collagen fibers are the most abundant elements of the ECM in the lung, constituting approximately 70% of the lung tissue, and changing the structure, quantity, or geometry of their distribution can trigger changes in lung functioning [58,59,60].…”
Section: Airway Remodeling In Asthmamentioning
confidence: 99%
“…Several studies using these experimental models of asthma have shown functional alterations in the resistance and elasticity of the respiratory system associated with inflammatory eosinophilic infiltrates; expression of Th2 and Th17 cytokines, MMP-9-, MMP-12-, TIMP-1-, and TGF-β-positive cells; increased deposition of actin, collagen, and elastic fibers, and increased mucus production in the airways and lung tissues [57,59,60,69,85].…”
Section: Airway Remodeling In Asthmamentioning
confidence: 99%
“…However, we aimed to evaluate the asthmatic and healthy eosinophil effect on ASMC and PF contractility and differentiation into the contractile phenotype, and collagen gel assay allows to evaluate the influence of eosinophils on ASMC/PF-induced collagen gel shrinkage [18]. Several studies confirmed that collagen gel assay is an appropriate method to evaluate the ASMC and PF contractility in changing environmental conditions such as adding contraction stimulating or inhibiting factors, thus providing a model for tissue contraction [90][91][92][93]. In the current study, we used eosinophils as a contraction of structural lung cells stimulating factor.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors such as matrix metalloprotein (MMP), especially MMP-9, MMP-12, or Rho-kinase (ROCK) proteins, contribute to the remodeling process as well by degrading the components of the ECM. Several studies (Bortolozzo et al, 2018;Righetti et al, 2014) using ovalbumin (OVA)-induced models of asthma have shown functional and structural alterations in the respiratory system associated with the high expression of TGF-β, MMP-9, MMP-12 positive cells, and Th2 cytokines: the increased deposition of actin and elastic fibers, and increased mucus production among big and small airways. The functional consequences of these alterations mostly result in the obstruction of small airways, airways narrowing, and the depressing of lung function due to sputum secretion (Ito et al, 2019).…”
Section: Airway Inflammation and Remodeling Factorsmentioning
confidence: 99%